2013
DOI: 10.1103/physrevstab.16.071002
|View full text |Cite
|
Sign up to set email alerts
|

Direct amplitude detuning measurement with ac dipole

Abstract: In circular machines, nonlinear dynamics can impact parameters such as beam lifetime and could result in limitations on the performance reach of the accelerator. Assessing and understanding these effects in experiments is essential to confirm the accuracy of the magnetic model and improve the machine performance. A direct measurement of the machine nonlinearities can be obtained by characterizing the dependency of the tune as a function of the amplitude of oscillations (usually defined as amplitude detuning). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…While poor agreement of these terms in the detuning expansion may be indicative of a poor quality fit or bad data, a good agreement does not necessarily imply the reverse. Recent theoretical advances, verified experimentally in the LHC, now allow for the study of amplitude detuning using an AC dipole kicker magnet [23]. As opposed to measurements with a single kick this has the advantage of being nondestructive, however the analysis is substantially complicated with respect to the single kick method and data quality may be lower.…”
Section: Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…While poor agreement of these terms in the detuning expansion may be indicative of a poor quality fit or bad data, a good agreement does not necessarily imply the reverse. Recent theoretical advances, verified experimentally in the LHC, now allow for the study of amplitude detuning using an AC dipole kicker magnet [23]. As opposed to measurements with a single kick this has the advantage of being nondestructive, however the analysis is substantially complicated with respect to the single kick method and data quality may be lower.…”
Section: Ordermentioning
confidence: 99%
“…It has been observed in simulations of detuning with amplitude at top energy in the LHC, that the linear coupling could significantly influence the nonlinear phenomenology of the machine [23]. The quality of the linear coupling model is therefore a particular concern for study of the nonlinear dynamics.…”
Section: Modeling the Lhc Nonlinearitymentioning
confidence: 99%
“…It is well known that the particle motion in the presence of forced oscillations differs from the free motion following a single kick. This has led to methods which account for this difference in the motion when reconstructing the optics parameters [9][10][11][12]. However, these studies stay at linear order in the strength of perturbing components and can therefore not be used to predict the ADeCTA.…”
Section: Introductionmentioning
confidence: 99%
“…However, upon reduction of the LHC β Ã from 1 to 0.6 m in 2012, a significant degradation of the beam lifetime was observed [12]. Optics studies at injection [13] and top energy [14] also revealed larger than expected discrepancies between the measured and predicted first and second order amplitude detuning. Nonlinear errors in the triplets and separation dipoles are one of several candidates for the source of these reductions in performance.…”
Section: Introductionmentioning
confidence: 99%